Socioeconomic potential for rainwater harvesting systems in southern Brazilian municipalities. Issue 1 (1st September 2021) - Tavares, L. C.; Bravo, J. M.; Tassi, R.; Almeida, I. R.; Wartchow, D.
Abstract: The implementation of rainwater harvesting (RWH) systems depends on technical and socioeconomic assessments. However, most studies do not consider socioeconomic aspects, which could lead to different degrees of RWH implementation and technology selection due to economic constraints and local regulations. We evaluated the socioeconomic potential for RWH as an alternative for the water supply of 24 southern Brazilian municipalities with less than 50, 000 inhabitants. A total of 10, 080 RWH configurations were assessed and a reliability analysis was carried out to define the RWH system configurations potentially implementable (RWH+) in each municipality. RWH economic benefits were estimated from a social point of view, based on the reduction of the monthly water payment. Overall, RWH+ supplying higher demands with higher economics savings were feasible, as expected. However, several municipalities that showed RWH+ supplying 100% of the domestic water demands obtained lower economic savings, due to low water tariff and water consumption. Still, a set of municipalities presented RWH+ for rainwater demand replacing 50% to 60% of the residential demand, for which the high water tariffs were reflected in higher economic savings. The advantages of using the RWH systems stand out even more when the investments at Federal and Local levels are considered. HIGHLIGHTS: Socioeconomic potential for rainwater harvesting in 24 Brazilian municipalities. 10, 080 system configurations were assessed for demand, rooftop area, tank capacity. System configuration was implementable if it reached at least 80% reliability. Economic savings of water payment were influenced by water tariff and consumption. The advantages of using rainwater stand out when the investments are considered.